Pengaruh Green Product Terhadap Repurchase Intention yang Dimediasi Oleh Brand Image pada Fore Coffee di Kota Makassar (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to determine the effect of Green Product on Repurchase Intention mediated by Brand Image at Fore Coffee in Makassar. The type of research used is explanatory research, which tests causal relationships between variables through hypothesis testing. The sampling technique employed is non-probability sampling using the purposive sampling method. The sample consists of 106 respondents. Data were collected through questionnaires, and data analysis was conducted using Partial Least Square (PLS) with the help of SmartPLS 3.0 software. The results of the study indicate that (1) Green Product has a positive but not significant effect on Repurchase Intention, (2) Green Product has a positive and significant effect on Brand Image, (3) Brand Image has a positive and significant effect on Repurchase Intention, and (4) Green Product has a positive and significant effect on Repurchase Intention through Brand Image.